Association of a new FCN3 haplotype with high ficolin-3 levels in leprosy. - Fabiana Antunes Andrade; Marcia Holsbach Beltrame; Valéria Bumiller Bini; Letícia Boslooper Gonçalves; Angelica Beate Winter Boldt; Iara Jose de Messias-Reason (Public Library of Science (PLoS), 2017)
Leprosy is a chronic inflammatory disease caused by Mycobacterium leprae that mainly affects the skin and peripheral nervous system, leading to a high disability rate and social stigma. Previous studies have shown a contribution of genes encoding products of the lectin pathway of complement in the modulation of the susceptibility to leprosy; however, the ficolin-3/FCN3 gene impact on leprosy is currently unknown. The aim of the present study was to investigate if FCN3 polymorphisms (rs532781899: g.1637delC, rs28362807: g.3524_3532insTATTTGGCC and rs4494157: g.4473C>A) and ficolin-3 serum levels play a role in the susceptibility to leprosy. We genotyped up to 190 leprosy patients (being 114 (60%) lepromatous), and up to 245 controls with sequence-specific PCR. We also measured protein levels using ELISA in 61 leprosy and 73 controls. FCN3 polymorphisms were not associated with disease, but ficolin-3 levels were higher in patients with FCN3 *2B1 (CinsA) haplotype (p = 0.032). Median concentration of ficolin-3 was higher in leprosy per se (26034 ng/mL, p = 0.005) and lepromatous patients (28295 ng/mL, p = 0.016) than controls (18231 ng/mL). In addition, high ficolin-3 levels (>33362 ng/mL) were more common in leprosy per se (34.4%) and in lepromatous patients (35.5%) than controls (19.2%; p = 0.045 and p = 0.047, respectively). Our results lead us to suggest that polymorphisms in the FCN3 gene cooperate to increase ficolin-3 concentration and that it might contribute to leprosy susceptibility by favoring M. leprae infection.